Efficiency of higher education institutions management and the labour market situation of graduates - an assessment of relations based on structural equation modelling (SEM) - Gawrysiak, Maciej; Stepien, Sebastian; Polcyn, Jan (Zielona Góra: Faculty of Economics and Management Press)
The aim of this publication is to assess the relationship between the effectiveness of university management and the graduale`s position on the labor market. The implementation of the goal serves to verify the following hypothesis: the higher the effectiveness of educational institutions, the better the graduate's position on the labor market.
Keywords: labour market; higher education institutions; relations; management efficiency; SEM modelling